Academic social responsibility : sine qua non for corporate social performance - Stachowicz-Stanusch, Agata; Amann, Wolfgang (Emerald Publishing Limited : Information Age Publishing Inc., 2018)
"The book Academic Social Responsibility - Sine Qua Non for Corporate Social Performance is our endeavor to disseminate the awareness of the significance of responsible (especially management) education not only for academic stakeholders, but for the whole society. It is an interesting combination of theories, studies, recognitions, and experiences gained by authors from different countries, institutions, who function in various institutional and cultural conditions. The book is divided into "Introduction" and three parts: "Towards the Socially Responsible University", "Socially Responsible Education for Enterprise Development", "Human Voice in Responsible Management Education". There are presented general concepts of socially responsible university, its impact on real business performance as well as there are discussed some specific and detailed problems of implementing academic social responsibility into practice"-- Provided by publisher.
Keywords: Business schools.; Business education -- Social aspects.; Management -- Study and teaching.; Social responsibility of business.; Universities and colleges -- Social aspects.; Business & Economics -- General.; Business studies: general.; Business and Management.; elektronické knihy; electronic books